Factors Affecting Hydrogen Adsorption in Metal–Organic Frameworks: A Short Review - Zeleňák, Vladimír (Nanomaterials (Basel), 2021)
Metal–organic frameworks (MOFs) have significant potential for hydrogen storage. The main benefit of MOFs is their reversible and high-rate hydrogen adsorption process, whereas their biggest disadvantage is related to their operation at very low temperatures. In this study, we describe selected examples of MOF structures studied for hydrogen adsorption and different factors affecting hydrogen adsorption in MOFs. Approaches to improving hydrogen uptake are reviewed, including surface area and pore volume, in addition to the value of isosteric enthalpy of hydrogen adsorption. Nanoconfinement of metal hydrides inside MOFs is proposed as a new approach to hydrogen storage. Conclusions regarding MOFs with incorporated metal nanoparticles, which may be used as nanoscaffolds and/or H(2) sorbents, are summarized as prospects for the near future.